(untitled) (Research, Society and Development, 2020)
Introduction: Several policies were created in order to rescue humanized care in the health-disease process, however, an individual involvement of professionals is necessary to achieve this humanization. Objective: To analyze the perception of humanization from the perspective of the professional nurse and the user. Materials and methods: This is a field research, with an exploratory qualitative approach, carried out at Hospital Dom Pedro de Alcântara in Feira de Santana-BA, during the month of October 2019. A questionnaire was applied to five nurses and six users hospitalized in the oncology sector. Results and Discussions: After reading the semi-structured questionnaires, the data were extracted and grouped according to the answers and presented in two tables so that the reader can understand the sociodemographic profile of the nurses and the participating users. In addition, four categories of subjects were organized (Perception of humanization; Academic training and humanization; Humanization in practice; Looking at the nurse) that emerged in the responses of participants in the format of tables to favor the organization of fragments of speeches, and then discussed in the light of relevant literature. Conclusion: The perception of humanization in the different views that the present study sought to investigate reveals that there is a big difference from the perspective of the professional nurse in relation to the user.